Modelling and control of refrigeration systems: an account of a pedagogic experiment in a post-secondary technical course - Duarte, Rogério (My University, 2016)
Traditional post-secondary technical training focuses on laboratory work, on hands-on experience, rather than on conveying theoretical knowledge. However, theoretical knowledge is and will remain an important asset for technical professionals working in the refrigeration industry. This paper presents an account of a pedagogic experiment in which advanced analytical methods and scientific computational tools were used in a post-secondary technical course to study the modelling and control of refrigeration systems. Targeted learning outcomes, topics taught, computational tools used, and the way topics and tools were aligned to meet the learning outcomes are described. Results gathered between 2012 and 2015 showed that the use of advanced topics to model simple thermal systems and simple control systems is possible in a post-secondary technical course. It is argued that levelling up the contents in post-secondary education to match those presented in higher education contributes to a better understanding of the challenges of higher education, and, for students that ponder enrolling in higher education, contributes to better informed decision making. If the growth in refrigeration industry is taken into account and considering future needs for skilled refrigeration professionals, introducing students of post-secondary technical courses to analytical methods and computational tools used in higher education could, for some students, trigger the decision to enrol in higher education, leveraging the number graduates in refrigeration/ engineering bachelor programmes.
Comunicação apresentada no CYTEF 2016/VIII Congresso Ibérico | VI Congresso Ibero-Americano de Ciências e Técnicas do Frio, 3-6 maio 2016, Coimbra, Portugal
Keywords: Post-secondary education; Higher education; Refrigeration; Modelling; Control